Arūnas Sverdiolas and the Phenomenological Philosophy of Culture - Jonkus, Dalius (Problemos, 2020)
The article deals with the relationship of hermeneutics and phenomenology in Arūnas Sverdiolas’s philosophy of culture. Firstly what is discussed is the problem of the separation between culture and nature, and then the concept of cultural activity and creation is analyzed. In cultural philosophy it is not enough to reflect on the cultural act of creation. Creation is the discovery of the world’s essential forms of expression. Ideas need to be discovered and only then they can be materialized and communicated to others in such an objective way. Therefore, culture must be understood as the communication of meaning. Cultural objects refer not only to the actions that create them, but also to the demands placed on potential perceivers.